1993
DOI: 10.1016/0032-3861(93)90729-t
|View full text |Cite
|
Sign up to set email alerts
|

Free radical polymerization of styrene in dioctadecyldimethylammonium bromide vesicles

Abstract: The novel radical polym erization of an unsaturated m onom er in the hydrophobic p a rt o f vesicles is attempted using the experience gathered from kinetic a n d thermodynamic studies o f the e m ulsion polym erization process. The influence of the m onom er content of the system and also the in itia tio n of the polym erization are discussed. A free radical polym erization of styrene in d io ctadecyldim ethylam m om um brom ide vesicles is performed. Evidence of the form ation of polymer-containing vesicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 19 publications
1
69
3
Order By: Relevance
“…Attention has been focused on the unusual electronic [2,3] and mechanical [4,5] properties predicted for these materials.…”
Section: Methodsmentioning
confidence: 99%
“…Attention has been focused on the unusual electronic [2,3] and mechanical [4,5] properties predicted for these materials.…”
Section: Methodsmentioning
confidence: 99%
“…No separate monomer phase could be detected and the vesicle dimensions remained constant within experimental accuracy during the swelling and subsequent polymerization. [8,9] From this it was concluded that the polymerization really occurred in the interior of the bilayer and under retention of the vesicle structure. Kinetic studies on a similar system revealed that the free-radical polymerization (of alkylacrylates) in vesicles is a very fast reaction: [10] the monomers are present locally, within the bilayer, at a rather high concentration and, perhaps, also have a favorable orientation for the chain reaction.…”
mentioning
confidence: 97%
“…Therefore, their lateral mobility, the phase behavior, and even the permeability of such membranes have been found to be not significantly changed by the presence of the polymer. [8,9] An interesting possibility for studying the properties of these polymer-stabilized membranes in more detail is to use planar lipid bilayers, so-called black lipid membranes (BLMs), as model systems.…”
mentioning
confidence: 99%
“…Successful intrabilayer swelling of vesicles with hydrophobic monomers and subsequent radical polymerization have been reported. [16][17][18][19][20] temperatures. These studies indicate that rearrangement of the amphiphilic molecules is possible and brought on by phase separation upon swelling which leads us to believe that more drastic morphological transformations of (polymer) vesicles can be induced.…”
mentioning
confidence: 99%